Teater Wayang Inovatif Satya Semara - Wira Adi; I Nyoman Sedana; I Bagus Wijna Bratanatya (Pusat Penerbitan LP2MPP ISI Bali, 2026)
The declining interest in traditional puppetry among younger generations and the growing demand for adaptive artistic forms have encouraged the need for innovative approaches to Balinese wayang performance. This study aims to describe the creation process, artistic realization, and interpretative strategy of the innovative wayang theater Satya Semara, which reinterprets the value of loyalty within the contemporary narrative of the Ramayana. The creation process employed the Catur Datu Kawiya method, consisting of Pandulame (imaginative exploration), Adicita Adirasa (conceptual formulation), Saranasasmaya (artistic media preparation), and Gunagina Gunamanta (collaborative realization). The artistic outcome presents a hybrid theatrical form integrating Ramayana puppetry, colossal performance, digital lighting, multimedia elements, and contemporary dramaturgy while maintaining essential values of Balinese puppetry. Through the reinterpretation of characters and dramatic tensions, Satya Semara offers a reflective reading of fidelity, sacrifice, and moral dilemmas in contemporary society. This creation contributes to the revitalization of Balinese puppetry through innovative performance strategies that preserve tradition while expanding its aesthetic and pedagogical relevance.